Analisis Pengaruh Investasi Penanaman Modal Asing Dan Pdrb Terhadap Pengangguran Terbuka Di Provinsi Kalimantan Barat - Maharani, Nuraprillia Dezta; Samsuddin, M. Afdal (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the influence of Domestic Investment (PMDN) and Gross Regional Domestic Product (GRDP) on the Open Unemployment Rate (OUR) in West Kalimantan Province during the period of 2019–2023. The research employs a quantitative approach using panel data regression with the Fixed Effect Model (FEM) to examine causal relationships among variables. The dataset consists of 14 districts/cities over five years, sourced from official publications by the Central Bureau of Statistics (BPS) and the Investment Coordinating Board (BKPM). The results reveal that individually, both PMDN and GRDP do not have a statistically significant effect on OUR. However, simultaneously, both variables significantly affect OUR, contributing to 82.11% of the variation. These findings indicate that the effectiveness of investment and economic growth in reducing unemployment is highly influenced by contextual factors such as sectoral composition, interregional disparities, and the nature of investment. Therefore, regional economic development strategies in West Kalimantan should prioritize labor-intensive and inclusive sectors that can create equitable employment opportunities across districts.